IMPLEMENTASI KEGIATAN LSLC TERHADAP AKTIVITAS PESERTA DIDIK SEBAGAI DASAR MENENTUKAN MODEL PEMBELAJARAN - Umi Khulsum; Rindawati; Dwi Susilowati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to identify effective learning models through the implementation of LSLC activities that influence student activities. The research was carried out in three cycles, each involving two open classes. The research sample consisted of phase D students, especially grade 8 at SMP Negeri 34 Surabaya, in science and technology subjects. The student activity criteria were adapted from Singarimbun, which includes: 1) a score of 1 for very inactive; 2) score 2 for inactive; 3) score 3 for less active; 4) value 4 for active; and 5) score 5 for very active. Data was collected through observations by observers during open classes. Data analysis was carried out descriptively and quantitatively by describing the number and percentage of active students. The results of observations regarding student activities are discussed in reflection sessions and used as a basis for determining the next learning model. This research applies the Problem Based Learning (PBL) model using media such as pictures, colored objects, guided inquiry approaches, practice, role playing, and project-based models. The participation rate of active to very active students reached 95%, which is the highest result in the project-based model. Differences in activity were analyzed using One-Way ANOVA with the help of SPSS v25. The results of the analysis show an R Square value of 0.928, which shows that student activity has increased due to the influence of the learning model by 92.8%. "The ANOVA test shows a significance value (Sig) of 0.000, and the coefficient test also produces a Sig value of 0.000, which shows that the learning model has a significant influence on student activities."   Keywords: student activities, guided inquiry, project based learning, Problem Based Learning (PBL)